Diplodia corticola and Phytophthora cinnamomi : the main pathogens involved in holm oak decline on Caprera Island (Italy) - Linaldeddu, B. T.; Scanu, B.; Maddau, L.; Franceschini, A. (Forest Pathology, 2014)
Since 2008, severe and widespread tree decline and mortality has been observed at the main growing Quercus ilex L. (holm oak) forest on Caprera Island, Italy. To clarify the symptomatology and aetiology of this phenomenon, field surveys and isolations from symptomatic trees were carried out in summer 2010. Affected trees exhibited crown thinning, branch dieback, sunken cankers, epicormic shoots, exudates on branches and trunk, root losses and sudden death symptoms. Four fungal species belonging to Botryosphaeriaceae family, namely Botryosphaeria dothidea, Diplodia corticola, D. seriata and Neofusicoccum parvum, were isolated from cankers on trunk and branches, whereas three species of Phytophthora, namely P. cinnamomi, P. cryptogea and P. gonapodyides, were isolated from fine roots and rhizosphere soil samples. Isolates were identified using both morphological analysis and DNA-based techniques. Pathogenicity trials on holm oak seedlings showed that all the isolated species are pathogenic. D. corticola proved to be the most aggressive species. Our results provide the first evidence for a combined involvement of D. corticola and P. cinnamomi in the aetiology of holm oak decline in Italy and suggest that these pathogens are not only important contributing factors in the onset of long-term tree decline, but also may cause the rapid devastation of extensive oak ecosystems.
Key words by Adriana SilvaKey words by Adriana SilvaThe following values have no corresponding Zotero field: label: APS;Quercus ilex L.;fungus;mortality;pathogens;tree decline
Keywords: APS; Fungus; mortality; pathogens; Quercus ilex L.; tree decline

Phytotoxins produced by the oak pathogen Discula quercina - Maddau, L.; Perrone, C.; Andolfi, A.; Spanu, E.; Linaldeddu, B. T.; Evidente, A. (Forest Pathology, 2011)
Two phytotoxic metabolites, p-hydroxybenzaldehyde and indol-3-aldehyde, were isolated and identified by spectroscopic methods from solid cultures of Discula quercina, an endophytic fungal pathogen frequently associated with oak decline in Italy. In addition, the fungus produced an unusual acyclic keto acid as a major metabolite, which was identified by spectroscopic and chemical methods as 5-oxo-6E,8E-octadecadienoic acid. In leaf puncture assays on Quercus suber and Q. ilex leaves, indol-3-aldehyde proved to be more toxic than p-hydroxybenzaldehyde, while 5-oxo-6E,8E-octadecadienoic acid was inactive even at the highest concentration used (1 mg ml−1). Although indol-3-aldehyde is a known microbial metabolite, its phytotoxic activity has hitherto not been reported. This report is the first to describe the production of phytotoxic compounds by D. quercina.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Discula quercina (voyant); Oak decline; phytotoxic metabolites

Variation of endophytic cork oak-associated fungal communities in relation to plant health and water stress - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2011)
The main objective of this study was to obtain more comprehensive knowledge about the eﬀect of water stress on endophytic fungal communities in asymptomatic and declining cork oak trees. Six asymptomatic and six declining cork oak trees were randomly selected in a natural cork oak forest located in Sardinia, Italy. In February 2003, the soil around three asymptomatic and three declining trees was covered with a circular plastic ﬁlm to reduce rain water supply with the intention to induce water stress. The remaining six trees served as controls. Predawn xylematic water potential (PWP) was used as water status indicator and measured seasonally. Between July 2003 and June 2004, fungal endophytes were isolated every 2–4 months from twigs, branches and woody tissues. Signiﬁcant diﬀerences in PWP between covered and control trees were detected mainly in autumn. Gas exchange was greatest in asymptomatic control plants. All tissues were colonized by endophytic fungi. Nineteen fungal species were isolated from 1620 plant fragments. Biscogniauxia mediterranea was the most frequently isolated fungus. Its isolation frequency was signiﬁcantly higher in declining covered trees than in control trees (p < 0.05). Presence of this fungus in asymptomatic control trees was signiﬁcantly higher in winter than in summer. Water stress seems to reduce species diversity of the endophytic mycobiota in cork oak and to promote proliferation of some potentially pathogenic endophytes.
Keywords: Cork oak; fungal endophytes; gas exchange and water potential (voyant); water stress

Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2009)
The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point; however, the lesions caused by B. corticola were longer in both oak species. On cork oak seedlings, all pathogens induced a signiﬁcant and gradual reduction in net photosynthesis and stomatal conductance values, whereas other physiological disturbances were induced only by B. corticola infections on holm oak seedlings.
Keywords: Cork oak; fungal pathogens; Holm oak; physiological responses (voyant); seedlings

First Report of Canker Disease Caused by Botryosphaeria parva on Cork Oak Trees in Italy - Linaldeddu, B. T.; Franceschini, A.; Luque, J.; Phillips, A. J. L. (Plant Disease, 2007)
A survey was carried out in the spring of 2003 to study the fungi associated with declining trees in a cork oak (Quercus suber L.) forest located in Sassari Province, Sardinia, Italy (40°52?N, 9°01?E) at an altitude of 150 m (above sea level). Several isolates obtained from live twigs and branches showing sunken necrotic bark lesions were identified as Fusicoccum parvum Pennycook EF1-α: 100%). Representative sequences of both regions were deposited at GenBank (ITS: Accession No. DQ487157; EF1-α: Accession No. DQ487158). Pathogenicity tests were carried out on seven 2-year-old cork oak seedlings maintained in a greenhouse at 14 to 26°C with the B. parva strain CBS 119937 obtained in this study. A mycelial plug (3 to 4 mm2) taken from the margin of an actively growing colony on PDA was put in a shallow wound made by a scalpel on the basal part of the stem of each seedling. Sterile PDA plugs were placed into similar wounds on three control seedlings. The inoculation points were wrapped in Parafilm to retain moisture for 1 week. After 4 weeks, all seedlings inoculated with B. parva died and showed a collapse of the stem cortical tissues associated with dark brown discolorations and vascular necrosis measuring 10.9 ± 0.4 cm. No symptoms were visible in the control seedlings. The pathogen was reisolated from all the inoculated seedlings, thus fulfilling Koch's postulates. The results confirm the virulence of this fungus and point to its possible involvement in the aetiology of cork oak decline. B. parva is a cosmopolitan, plurivorous pathogen causing disease in several hosts of economic importance, such as grapevine (3), kiwi (2), and Eucalyptus spp. trees (1). To our knowledge, this is the first report of B. parva causing canker disease on cork oak trees. References: (1) A. Gezahgne et al. S. Afr. J. Bot. 70:241, 2004. (2) S. R. Pennycook and G. J. Samuels. Mycotaxon 24:445, 1985. (3) A. J. L. Phillips. Phytopathol. Mediterr. 41:3, 2002. (4) B. Slippers et al. Mycologia 96:83, 2004.
doi: 10.1094/PDIS-91-3-0324Adoi: 10.1094/PDIS-91-3-0324AThe following values have no corresponding Zotero field: publisher: Scientific Societies
Keywords: canker disease; Cork oak; Italy (voyant)